Laser Ablation Ionization Mass Spectrometry: A Space Prototype System for In Situ Sulphur Isotope Fractionation Analysis on Planetary Surfaces - Riedo, Andreas; Grimaudo, Valentine; Aerts, Joost W.; Lukmanov, Rustam; Tulej, Marek; Broekmann, Peter; Lindner, Robert; Wurz, Peter; Ehrenfreund, Pascale (Frontiers in Astronomy and Space Sciences, 2021)
The signatures of element isotope fractionation can be used for the indirect identification of extant or extinct life on planetary surfaces or their moons. Element isotope fractionation signatures are very robust against the harsh environmental conditions, such as temperature or irradiation, which typically prevail on solar system bodies. Sulphur is a key element for life as we know it and bacteria exist, such as sulphur reducing bacteria, that can metabolize sulphur resulting in isotope fractionations of up to −70‰ δ34S. Geochemical processes are observed to fractionate up to values of −20‰ δ34S hence, fractionation exceeding that value might be highly indicative for the presence of life. However, the detection of sulphur element isotope fractionation in situ, under the assumption that life has existed or still does exist, is extremely challenging. To date, no instrument developed for space application showed the necessary detection sensitivity or measurement methodology for such an identification. In this contribution, we report a simple measurement protocol for the accurate detection of sulphur fractionation δ34S using our prototype laser ablation ionization mass spectrometer system designed for in situ space exploration missions. The protocol was elaborated based on measurements of five sulphur containing species that were sampled at different Mars analogue field sites, including two cave systems in Romania and the Río Tinto river environment in Spain. Optimising the laser pulse energy of our laser ablation ionization mass spectrometer (LIMS) allowed the identification of a peak-like trend of the 34S/32S ratio, where the maximum, compared to internal standards, allowed to derive isotope fractionation with an estimated δ34S accuracy of ∼2‰. This accuracy is sufficiently precise to differentiate between abiotic and biotic signatures, of which the latter, induced by, e.g., sulphate-reducing microorganism, may fractionate sulphur isotopes by more than −70‰ δ34S. Our miniature LIMS system, including the discussed measurement protocol, is simple and can be applied for life detection on extra-terrestrial surfaces, e.g., Mars or the icy moons like Europa.